Analisis Pengaruh Inovasi Produk Terhadap Keunggulan Bersaing Pada UKM â€œDuren Kamu Pasti Kembaliâ€ di Kota Serang - Hasnatika, Imas Fatimah; Nurnida, Ida (Jurnal Riset Bisnis dan Investasi, 2018)
The study was conducted to determine the effect of product innovation on competitive advantage at SME of â€œDuren Kamu Pasti Kembaliâ€ in Serang City. This study uses quantitative and was analyzed descriptively the hypothesis was tested by using simple linear regression analysis. This study uses descriptive research-causality. Sampling technique used was saturated sampling type under non-probability sampling, with the 19 respondents. Based on the results of testing the hypothesis with the t-test, product innovation significantly influenced on competitive advantage at SME â€œDuren KPKâ€ in Serang City. The results of coefficient of determination showed that product innovation at SME â€œDuren KPKâ€ was able to explain 77,8% competitive advantage, and the remaining 22,2% was influenced by other factors not examined in this research. The conclusion of this study is product innovation at SME â€œDuren KPKâ€ is categorized as good, but there are several aspects that need to be improved such as product innovation that is still easily imitated by other competitors, and the price of products that are not yet affordable.